2018
DOI: 10.3928/24748307-20180503-02
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Estimation of English and Spanish Language Caregivers

Abstract: Background: Provider ability to estimate caregiver health literacy (HL) in English-speaking caregivers has been shown to be poor, but estimation of HL in Spanish-speaking caregivers by physicians and staff has yet to be studied. Linguistic differences can further hinder communication in medical care. Objective: This study evaluated how well pediatric providers and staff predict caregiver HL as measured by two HL tools in a bilingual (English/Spanish) population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
(34 reference statements)
1
6
0
1
Order By: Relevance
“…There are ample data demonstrating that clinician assessment of health literacy of both patients and caregivers is poor ( Bass et al, 2002 ; Cooper et al, 2018 ; Kelly & Haidet, 2007 ), yet most physicians and especially residents felt they could adequately assess health literacy. Universal health literacy precautions were designed to reduce reliance on physician assessment or health literacy assessment tools to stratify the types of information given to patients and to ensure that all patients and caregivers received adequate information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are ample data demonstrating that clinician assessment of health literacy of both patients and caregivers is poor ( Bass et al, 2002 ; Cooper et al, 2018 ; Kelly & Haidet, 2007 ), yet most physicians and especially residents felt they could adequately assess health literacy. Universal health literacy precautions were designed to reduce reliance on physician assessment or health literacy assessment tools to stratify the types of information given to patients and to ensure that all patients and caregivers received adequate information.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, studies have also shown that not only do physicians have difficulty identifying caregivers or patients with limited health literacy, but pediatricians feel they have inadequate communication skills and time to meet the needs of these caregivers ( Bass et al, 2002 ; Chesser et al, 2012 ; Cooper et al, 2018 ; Kelly & Haidet, 2007 ; Turner et al, 2009 ). Additionally, research shows that residents overestimate the clarity with which they communicate and instead often use medical jargon and rarely use clear communication strategies such as Teach-Back techniques ( Howard et al, 2013 ).…”
mentioning
confidence: 99%
“…"24–28 Health literacy is widely recognised as a factor influenced by multiple social determinants of health including English proficiency, race, ethnicity, income and educational attainment 17 20. Its measurement may be particularly affected by language,18 29 30 such as whether health literacy is assessed in the predominant language of the healthcare organisation or in the patient’s native language. To overcome this challenge, some studies recommend assessing "confidence completing medical forms in English by yourself" 18.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, patients may be reluctant to reveal limited health literacy 31 32. Studies suggest that some patients—especially those with language preferences other than English— may poorly estimate health literacy 29 33. Low health literacy is associated with poor health outcomes in various populations,17 18 29 and may be exacerbated by limited English proficiency 18 30 34.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation